Komposit Aluminium 1100 ‐ Nano Alumina Metode Dispersi Mekanik Screen Printing dan Ultrasonic Fogger Accumulated Roll Bonding: Aluminum 1100 - Nano Alumina Composite with Mechanical Screen Printing and Ultrasonic Fogger Dispersion Method on Accumulated Roll Bonding Process - Riska Rachmantyo; Aditianto Ramelan; Firmansyah Sasmita (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2020)
Aluminum material that is commonly used in life. This material is lightweight, corrosion resistant, tough and good working process. However, strength and hardness are lower than other metals such as steel. Processing needs to be done to get better aluminum mechanical properties. In this study, making a metal matrix composite in which aluminum 1100 as a substrate and 10 nm nano alumina (Al2O3) powder as a reinforcement. The process of making composites uses the method of accumulated roll bonding. The distribution of alumina powder on the aluminum matrix greatly influences the mechanical properties produced, namely its strength and hardness. The distribution process of nano alumina is carried out using screen printing, spray and ultrasonic spray methods. Besides the distribution method, the amount of alumina is also used as a research parameter. Improved optimum mechanical properties were obtained from the ultrasonic spray spray distribution method with the addition of 5 w/0 alumina.